Analysing barriers to service improvement using a multi‐level theory of innovation: the case of glaucoma outpatient clinics. Issue 4 (13th February 2018) - Turner, Simon; Vasilakis, Christos; Utley, Martin; Foster, Paul; Kotecha, Aachal; Fulop, Naomi J.
Abstract: The development and implementation of innovation by healthcare providers is understood as a multi‐determinant and multi‐level process. Theories at different analytical levels (i.e. micro and organisational) are needed to capture the processes that influence innovation by providers. This article combines a micro theory of innovation, actor‐network theory, with organisational level processes using the 'resource based view of the firm'. It examines the influence of, and interplay between, innovation‐seeking teams (micro) and underlying organisational capabilities (meso) during innovation processes. We used ethnographic methods to study service innovations in relation to ophthalmology services run by a specialist English NHS Trust at multiple locations. Operational research techniques were used to support the ethnographic methods by mapping the care process in the existing and redesigned clinics. Deficiencies in organisational capabilities for supporting innovation were identified, including manager‐clinician relations and organisation‐wide resources. The article concludes that actor‐network theory can be combined with the resource‐based view to highlight the influence of organisational capabilities on the management of innovation. Equally, actor‐network theory helps to address the lack of theory in the resource‐based view on the micro practices of implementing change.